2017
DOI: 10.1098/rspb.2016.2588
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity is largely unpredictable but scales with museum occurrences in a species-rich clade of Australian lizards

Abstract: Genetic diversity is a fundamental characteristic of species and is affected by many factors, including mutation rate, population size, life history and demography. To better understand the processes that influence levels of genetic diversity across taxa, we collected genome-wide restriction-associated DNA data from more than 500 individuals spanning 76 nominal species of Australian scincid lizards in the genus Ctenotus. To avoid potential biases associated with variation in taxonomic practice across the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 65 publications
(115 reference statements)
8
49
1
Order By: Relevance
“…Our study reveals that a species‐rich community of related taxa displays the same positive diversity–abundance association found by other studies at both narrower and broader phylogenetic and geographical scales. The proportion of variance in genetic diversity that was explained by local‐scale abundance in the present study is similar to that explained by museum occurrence records (a proxy for global population size) in a recent study of genetic diversity in the lizard genus Ctenotus , a member of the Sphenomorphine clade that is represented in the current data set (Singhal, Huang et al, ). Similarly, Pearson correlations between abundance and diversity recovered from broader phylogenetic sampling and meta‐analyses in other taxa are also comparable to the correlation recovered here ( r = 0.4; Leimu et al, ; McCusker & Bentzen, ).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our study reveals that a species‐rich community of related taxa displays the same positive diversity–abundance association found by other studies at both narrower and broader phylogenetic and geographical scales. The proportion of variance in genetic diversity that was explained by local‐scale abundance in the present study is similar to that explained by museum occurrence records (a proxy for global population size) in a recent study of genetic diversity in the lizard genus Ctenotus , a member of the Sphenomorphine clade that is represented in the current data set (Singhal, Huang et al, ). Similarly, Pearson correlations between abundance and diversity recovered from broader phylogenetic sampling and meta‐analyses in other taxa are also comparable to the correlation recovered here ( r = 0.4; Leimu et al, ; McCusker & Bentzen, ).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have found positive relationships between heterozygosity and proxies for species abundance, including population size estimated from calculations of density and acreage (Patton & Yang, ), extrapolations calculated from active social groups (Stangel, Lennartz, & Smith, ), categorical estimates (“large,” “small”) of population size (Godt, Johnson, & Hamrick, ; Hague & Routman, ) and museum occurrence records (Singhal, Huang, et al, ). Studies that more directly compare intraspecific genetic diversity and abundance have reported positive associations, but these studies have generally focused on single species or paired species comparisons (Devillard, Santin‐Janin, Say, & Pontier, ; Lozier, ; Ortego, Aparicio, Cordero, & Calabuig, ; Sun, ), or on many species sampled at a broad geographical scale (Bazin, Glémin, & Galtier, ; Leimu, Mutikainen, Koricheva, & Fischer, ; McCusker & Bentzen, ; Pinsky & Palumbi, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations